Analisis Struktur Komunitas Fitoplankton di Beberapa Ekosistem Air Terjun Kecamatan Jabung, Kabupaten Malang - Salsabila, Dina; Catur Retnaningdyah; Yusuf, Muhammad (Biosel Biology Science and Education, 2026)
Phytoplankton are primary biotic components of aquatic ecosystems that are highly sensitive to environmental changes and are therefore widely used as biological indicators of water quality. However, information on phytoplankton community structure in waterfall ecosystems remains limited, particularly in tropical regions. This study aimed to analyze the phytoplankton community structure in waterfall ecosystems in Jabung district as a basis for assessing water quality. Sampling was conducted at four waterfall sites, namely Siuk, Tarzan, Toris, and Jahe, with three replicates at each location. Phytoplankton samples were collected by filtering 3 liters of water using a plankton net with a mesh size of 40 µm, then preserved with 4% formalin (10 drops) and CuSO₄ (5 drops). Identification and enumeration of phytoplankton were performed using 1 mL of sample placed in a Sedgewick–Rafter Counting Chamber and observed under a binocular microscope (100× magnification) across 1,000 fields of view. The collected data were used to calculate abundance, taxonomic richness, community composition, the Shannon–Wiener diversity index (H’), evenness index (E), and dominance index (D). The results showed that phytoplankton taxa were present in all observed waterfall ecosystems, consisting of Bacillariophyceae (21 genera), Chlorophyceae (9 genera), Cyanophyceae (5 genera), Zygnematophyceae (9 genera), and Trebouxiophyceae (1 genus). The highest diversity index was recorded at Jahe Waterfall (H’ = 4.50), while the lowest was found at Siuk Waterfall (H’ = 4.17). The highest evenness index occurred at Siuk Waterfall (E = 0.8773), with a dominance index value of 0.075. Overall, all sites exhibited high diversity (H’ > 3) and very low dominance, indicating that phytoplankton communities were stable and well balanced across all investigated waterfall ecosystems.  Keywords: Water Quality, Phytoplankton, Community, Waterfalls, Diversity